2018
DOI: 10.1016/j.neuropsychologia.2017.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the interrelationships between brain activity and trait attention measures to predict individual differences in reaction times in children during a Go/No-Go task

Abstract: Many researchers are utilizing event-related potentials (ERPs) to better understand brain-behavior relationships across development. The present study demonstrates how structural equation modeling (SEM) techniques can be used to refine descriptions of brain-behavior relationships in a sample of neurotypical children. We developed an exploratory latent variable model in which trait measures of maturation and attention are related to neural processing and task behaviors obtained during a cued Go/No-Go task. Mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Manly et al (2007) demonstrated that for 6-to 16-year-old Australian children, the age-standardized scores of the nine subtests can be combined into a three-factor configuration representing the three different types of attention, naming them as sustained, selective, and control/shift. In a more recent examination of the factor structure of the TEA-Ch conducted on children aged 6-13 years in the United States, the best-fitting model using structural equation modeling resulted in just two factors (Taylor et al, 2018). The first factor included the sustained subtests, and the second factor was a combination of the subtests representing both the selective and control/shift subtests.…”
Section: Test Of Everyday Attention For Children (Tea-ch)mentioning
confidence: 99%
See 4 more Smart Citations
“…Manly et al (2007) demonstrated that for 6-to 16-year-old Australian children, the age-standardized scores of the nine subtests can be combined into a three-factor configuration representing the three different types of attention, naming them as sustained, selective, and control/shift. In a more recent examination of the factor structure of the TEA-Ch conducted on children aged 6-13 years in the United States, the best-fitting model using structural equation modeling resulted in just two factors (Taylor et al, 2018). The first factor included the sustained subtests, and the second factor was a combination of the subtests representing both the selective and control/shift subtests.…”
Section: Test Of Everyday Attention For Children (Tea-ch)mentioning
confidence: 99%
“…This structure of selective and control/shift collapsing into one factor is supported by Petersen and Posner (2012) who suggest that the neural networks for selective and control/shift may not be differentiated in young children. Taylor et al (2018) named this combined factor control attention. Thus, the resulting two factors revealed in young children were sustained and control attention (Taylor et al, 2018).…”
Section: Test Of Everyday Attention For Children (Tea-ch)mentioning
confidence: 99%
See 3 more Smart Citations